A originalidade do vocabulário açoriano (Philology, 2026)
Portuguese language which is being spoken by Azorians is very much diversified as far as its phonological, morphological as well as lexical level is concerned. It seems that the diversification of the vocabulary on the islands is a result of a social and historical background in which different communities were being formed on each and every island separately during their population process in 15th century. The subsequent isolation of the entire archipelago as well as of individual islands throughout centuries might have influenced the current vocabulary which is rich in archaisms and words of a folk elements.The aim of this study is to analyze the vocabulary of the Azorean islands in particular of São Miguel and Terceira island which were two initially explored and populated islands on the Azorean archipelago.
Keywords: vocabulary; archaisms; Portuguese language; the Azores